Korstog mod de hedenske svenskere. Nye perspektiver på Kalmarledingen 1123/1124 - Jensen, Janus Møller (Collegium Medievale, 2019)
This article places the so-called Kalmar expedition 1123 or 1124 within the general framework of crusading activities and expeditions in the years 1120-1126 initiated by Pope Calixtus II. It argues that Denmark and Norway formed part of the political and family networks which played an important role in the extension and organization of the crusade in the first decades of the twelfth century. It thus contributes to the current debate concerning how crusade ideology was used and influenced conflicts in different frontier regions of Christendom in the first half of the twelfth century.